Detection of Bacterial Pollution from School Drinking Water Tanks in the Habbaniyah District West of Iraq - Najeeb, Laith Muslih; Shartooh, Sufyan Mohammed; Yaqob, Haidar Kadhum (Iraqi Journal of Science, 2024)
This study was conducted to evaluate the bacterial contamination in drinking water tanks from 20 randomly distributed primary schools in Habbaniyah district. The most probable number and the total plate count methods were used to determine the numbers of coliform, fecal coliform, streptococci and fecal streptococci. Chemical and physical properties of the water were measured, including residual chlorine, total dissolved solids, temperature and pH. Biochemical methods were used to detect various bacterial species contaminating the water samples and the results were confirmed using the VITEK 2 compact system. High levels of bacterial contamination were indicated. The highest value of coliform numbers reached 12 cells/100 ml. The total plate count recorded the highest values reaching 300 cells/ml. The concentration of residual chlorine was very low or non-detectable in most of samples below the required concentration and the concentrations of total dissolved solids exceeded the permissible limit (855 mg/L). The genetic relationship between environmental isolates of Escherichia coli bacteria from tank water and clinical isolates from children’s health centers were also studied. The results for Escherichia coli demonstrated a similarity ratio between environmental and clinical isolates of 64% by using dendrogram and Enterobacterial Repetitive Intergenic Consensus PCR. Nevertheless, this study recommends the need to monitor drinking water quality that supplies these reservoirs, as well as to prevent and treat problems that result in drinking water contamination and the spread of diseases.